The Role of International Environmental Law in Mitigating Climate Change: A Systematic Literature Review - Aris Krisdiyanto (Law Studies and Justice Journal (LAJU), 2024)
This research explores the role of international environmental law in climate change mitigation efforts through a systematic literature review. Evaluations are carried out on the effectiveness, challenges and opportunities related to various international legal instruments that have been adopted. The research method uses the PRISMA approach to identify and analyze relevant articles from international databases. The results of this research reveal the importance of global coordination in the implementation of international environmental law and its crucial role in supporting international cooperation in mitigating climate change.